Umowy dotyczące hipotecznych kredytów „walutowych” (tak zwanych frankowych) w „istotnych poglądach w sprawie” wydawanych przez Prezesa UOKiK - Rajchemba, Zygmunt (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article discusses the institution of the “significant view in the matter” issued by the President of the Office of Competition and Consumer Protection in cases pending before common courts in the field of competition and consumer protection introduced in April 2016 to the Act on Competition and Consumer Protection (Article 31d of the Act). The first part of the article describes the nature of issued views and the premises enabling their issuance by the President of UOKiK. The second part of thearticle focuses on the views expressed by the President of UOKiK on cases pending before common courts regarding foreign currency loans (CHF loans) together with the main elements of justification and conclusions, proposals of adjudicating the case by the court. The study refers to important views on the issue of currency loans (CHF) issued by the President of UOKiK, published on the website of the office: www.uokik.gov.pl
Keywords: hipoteka; pożyczki; waluta obca; umowa konsumencka; nieuczciwe warunki